The Influence of Problem Based Learning Model Assisted by Video on Student’s Problem-Solving Skills in Static Fluid Material - Al-Qoyyim, Thufail Mujaddid; Wahyudi, Wahyudi; Gunawan, Gunawan; Doyan, Aris (Journal of Science and Science Education, 2024)
This research aims to find out whether the problem-based learning (PBL) model, assisted by physics learning videos using static fluid material, influences students' problem-solving abilities. The population of this research was class XI students at SMAN 2 Mataram, with a sample of class 11 Science-Technology as the experimental class and class XI Science-Health as the control class. The data collection technique uses a problem-solving ability instrument in the form of 6-item description questions. The instruments used have been tested for their suitability through tests of validity, reliability, distinguishability and level of difficulty. Hypothesis testing uses an independent sample t-test with a significance level of 5% or 0.05 using the PSPP version 3 application. The results of the independent sample t-test show that a significance value of 0.002 is obtained. This means that the significance value is smaller than 0.005, so H0 is rejected, and Ha is accepted; in other words, the problem-based learning model assisted by physics learning videos using static fluid material influences students' problem-solving abilities.